Skrining Gangguan Ambang Pendengaran melalui Pemeriksaan Audiometri pada Penduduk di Sekitar PLTD Panangkalaan - Maharso Tedjo Oedono, Suharyanto Supardi (Berita Kedokteran Masyarakat (BKM), 2003)
Background: The inter relationship between man and their environment will make the functional relation, that can cause danger for the environment (environmental hazard). The danger of the environment will always be if there is residues and wastes which are the result of man activities, including the development activity of energy sources in the residential environment which is not managed well. This earlier survey which is done by Juhriadi (1998) found the trouble noise which is characterized non auditory effect has occured among the people who are living around PLTD Panangkalaan, the regency of Hulu Sungai Utara, South Kalimantan. It is also supported by Braveman and Tarimo (1994) that many risk psychosocial factors that can cause health problem, concerning with hearing problems, therefore there is an enough reason to screening with audiometri for the people around PLTD Panangkalaan.Objective: The general aims of the research is to know proprotion of hearing problem of the people who living around PLTD Panangkalaan.Methods: The methods uses observational study with cross sectional design. Results: Proportion of hearing problem about 85% among subject who's 23 to 76 years old, and audiogram patterns of subject research showed that there was a trouble indication in the conduction deafness. The measured to be continue with bone conduction method among sub sample (25 subject), showed that among 17 subject who's < 50 years old, 4 subject were have trouble indication sensori-neural deafness. The audiogram pattern like the socioacusis (sensori-neural deafness). The noise exposure function which is cause by PLTD was certain because we know the bone conduction audiogram. Conclusions: The research can be continued with case control study and clinical audiometri for the cases. Keywords: Audiometri screening – Residential noisy